Induction of an anti-tumor immune response by sonodynamic therapy, combining 5-aminolevulinic acid and high-intensity focused ultrasound using the trigger pulse sonication - Tohru Satoh; Rui Tada; Taiki Yamaguchi; Yoko Endo-Takahashi; Takashi Kanno; Mai Hayakawa; Yoshiyuki Adachi; Yoichi Negishi; Jun Okamoto; Shin Yoshizawa; Ken Masamune (WFUMB Ultrasound Open)
Ultrasound-based cancer therapies offer non-invasive treatment options for deep-seated tumors, yet their clinical application is often limited by safety concerns. High-intensity focused ultrasound (HIFU) has demonstrated therapeutic potential, but its high-power requirements can damage surrounding healthy tissues, particularly near sensitive structures such as the gastrointestinal tract. The optimal balance between therapeutic efficacy and safety remains a significant challenge in ultrasound-based cancer treatment. Here we show that combining 5-aminolevulinic acid (5-ALA)-mediated sonodynamic therapy (SDT) with a novel HIFU system achieves effective tumor suppression at reduced acoustic intensities while enhancing anti-tumor immune responses. This novel system features the use of a trigger HIFU sequence that enables precise control over cavitation bubbles within the target tissue. In a murine colon carcinoma model, this approach demonstrated significant tumor growth inhibition with single-session treatment comparable to multiple HIFU sessions, while increasing tumor infiltration by activated CD8+ T cells and antigen-presenting dendritic cells. These findings extend beyond previous studies by revealing that SDT not only enables effective tumor treatment at lower, safer acoustic intensities but also promotes beneficial immune responses that could enhance therapeutic outcomes. This combination of reduced treatment intensity, shortened duration, and immune system activation suggests potential applications for treating tumors in anatomically sensitive locations. The demonstrated immunological effects also indicate possible synergies with existing cancer immunotherapies, potentially expanding treatment options for patients with deep-seated solid tumors.